Implementation of Competitive Adaptation and Resilience Strategies Post Covid-19 Pandemic in Halal Food SMEs - Haque, Marissa Grace (Universitas Airlangga, 2024)
SME industry saves the nation's economy, 10.79 million people (7.71 percent) of the Indonesian population work in providing accommodation and food. Knowing the survival ability of industry players on a mike scale is very important. This study used a mixed method, with descriptive analysis to determine the survival ability of the